On nonlinear procedure for obtaining length - weight relationship - Venugopalan, R; Pragneshu, Pragneshu (The Indian Journal of Animal Sciences, 2012)
A comparative study of linear and non-linear parameter estimation procedures for allometric model describing thelength - weight relationship is carried out. It is shown that the latter approach is the correct one from statistical point ofview. It is demonstrated. by an illustration, that the proposed procedure may yield parameter estimates which are notonly quantitatively different from the corresponding ones for linear estimation but also have a bearing on the biologicalinterpretation